‘Strategic funnels’: deciphering Indonesia’s submarine ambitions - Ristian Atriandi Supriyanto (2016)
Historical experience, archipelagic geography, and strategic imperative make submarines a critical asset for Indonesia’s naval defence in spite of financial and other constraints. Overambitious submarine projects, however, are perilous.